Smart hybrid isolation of a case study highway bridge exploiting seismic early warning information. (15th September 2017) - Nuzzo, Iolanda; Caterino, Nicola; Maddaloni, Giuseppe; Occhiuzzi, Antonio
Highlights: Application of a complex framework early warning-smart magnetorheological system for a case-study bridge retrofit. Description of the regional control algorithm allowing to perform a real-time optimization of smart dampers through the use of a Seismic Early Warning System. The control strategy provides a structural protection not only to the bridge subjected to a mean seismic action but also in correspondence of each individual expected earthquake. Abstract: An innovative technique for seismic retrofit of a case study highway bridge is presented herein. It is done by means of the friction pendulum isolators (FPS) combined with smart magnetorheological dampers (MR), the latter calibrated through the use of a Seismic Early Warning System (SEWS). Hybrid systems, widely investigated by researchers in last years, generally represent a suitable solution in case of base-isolated bridges. As a matter of facts, the introduction of an isolation system allows to reduce shear and bending moment in piers, but may increase decks' relative displacements. A possible effective strategy for limiting this undesired effect may be the adoption of a dissipative system. Herein the passive smart use of MR devices is proposed. The MR dampers are smart in the sense that their mechanical properties can be tuned almost in real time, once before the earthquake strikes the site. A properly designed control algorithm modifies dampers' characteristics according to the intensity of the seismic event is going to occur, as forecasted by the SEWS. This retrofit strategy makes the structure someway adaptive, leading to a significant enhancement of the seismic performance against earthquakes even very different one each other. The case study is an existing reinforced concrete highway bridge built in the 70's, located in the city of Naples, southern Italy.